PEC 32/2020: its conception of the state and criticism of the loss of more rights in the public service in Brazil (Research, Society and Development, 2022)
The objective of this article is to present the proposal of PEC 32/2020, in order to understand its main proposals, with a view to clarifying the process of greater privatization and commodification of the State, foreseen with this PEC, which brings more loss of rights, which it intends to impose, if approved, along with the public service in Brazil. It also demonstrates that PEC 32/2020 brings a sequence of proposals for neoliberal actions aimed at reducing the State's responsibility and that it does not resolve any of the distortions that it proposed to analyze, on the contrary, it proposes the reduction of the autonomy of public servants, making them government employees and not state employees, as well as corroborating the total discouragement of hiring qualified and also motivated civil servants, having as a consequence, if approved, a reduction in the supply and quality of public servants.